The effect of cilostazol on carotid intima-media thickness progression in patients with symptomatic intracranial atherosclerotic stenosis - Bum Joon Kim (2018)
The progression of carotid intima-media thickness (CIMT) is closely associated with ischemic stroke recurrence. However, the efficacy of cilostazol on preventing CIMT progression in stroke patients has never been investigated properly by a prospective trial. Methods: This study is a part of "Trial of Cilostazol in Symptomatic Intracranial Arterial Stenosis-2." Six centers that are available to measure CIMT according to the protocol participated in this substudy. After 7 months of randomization, the changes of CIMT were compared between cilostazol group and clopidogrel group. CIMT was measured by a semiautomated software (Intimascope) and was presented as the mean of maximum (CIMT-max) and average (CIMT-ave) of both common carotid arteries. Linear logistic regression analysis and analysis of covariance were performed to verify the independent factors associated with CIMT progression. Results: Among the 85 patients, 39 subjects were assigned to cilostazol group and 46 subjects to clopidogrel group. Follow-up CIMT significantly decreased in cilostazol group (CIMT-max: -.03 ±.11 and CIMT-ave: -.02 ±.08) compared with the increase in clopidogrel group (CIMT-max:.04 ±.20 and CIMT-ave:.04 ±.11; P =.05 and P =.04, respectively). Female, diabetes, and smoking were independently associated with the progression of CIMT, whereas the use of cilostazol was against CIMT progression from the results of linear regression analysis (P =.03 for both CIMT-max and CIMT-ave). The use of cilostazol also well predicted less progression of CIMT at follow-up after adjusting for baseline CIMT values and conventional risk factors (CIMT-max: P =.04 and CIMT-ave: P =.03). Conclusion: Cilostazol has a beneficial effect in preventing the progression of CIMT in ischemic stroke patients. © 2014 by National Stroke Association.